Rosette-Disrupting Effect of an Anti-Plasmodial Compound for the Potential Treatment of Plasmodium falciparum Malaria Complications (2016)
The spread of artemisinin-resistant parasites could lead to higher incidence of patients with malaria complications. However, there are no current treatments that directly dislodge sequestered parasites from the microvasculature. We show that four common antiplasmodial drugs do not disperse rosettes (erythrocyte clusters formed by malaria parasites) and therefore develop a cell-based high-throughput assay to identify potential rosette-disrupting compounds. A pilot screen of 2693 compounds identified Malaria Box compound MMV006764 as a potential candidate. Although it reduced rosetting by a modest 20%, MMV006764 was validated to be similarly effective against both blood group O and A rosettes of three laboratory parasite lines. Coupled with its antiplasmodial activity and drug-likeness, MMV006764 represents the first small-molecule compound that disrupts rosetting and could potentially be used in a resource-limited setting to treat patients deteriorating rapidly from malaria complications. Such dual-action drugs that simultaneously restore microcirculation and reduce parasite load could significantly reduce malaria morbidity and mortality.